2013
DOI: 10.1111/jvs.12062
|View full text |Cite
|
Sign up to set email alerts
|

Direct and size‐dependent effects of climate on flowering performance in alpine and lowland herbaceous species

Abstract: Questions Effects of climate on flowering performance are often investigated independently of plant size. We ask how temperature and precipitation impact flowering probability and flower production: via direct effects, size‐dependent indirect effects, changes in minimum size for flowering and/or changes in reproductive investment. Location Twelve calcareous grasslands in western Norway (4°50′–8°45′ E, 60°20′–61°50′ N). Methods The investigations were carried out at the rear temperature edge of alpine plants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Our study showed distinct responses in flowering onset time to a 15% increase in precipitation and the magnitude of the responses was dependent on plant life‐history strategy. Spring ephemerals generally showed advanced flowering onset time by 0.3–5.2 days in our study, which falls within previously reported ranges (Cleland et al., ; Liu, Monaco et al., ; Meineri et al., ; Xia & Wan, ). However, two spring‐summer annuals showed opposite responses to water addition, with a delay in flowering onset of 5.9–13.3 days in C. arenarius but an advanced flowering onset of 5.9–10.7 days in S. brachiate .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed distinct responses in flowering onset time to a 15% increase in precipitation and the magnitude of the responses was dependent on plant life‐history strategy. Spring ephemerals generally showed advanced flowering onset time by 0.3–5.2 days in our study, which falls within previously reported ranges (Cleland et al., ; Liu, Monaco et al., ; Meineri et al., ; Xia & Wan, ). However, two spring‐summer annuals showed opposite responses to water addition, with a delay in flowering onset of 5.9–13.3 days in C. arenarius but an advanced flowering onset of 5.9–10.7 days in S. brachiate .…”
Section: Discussionsupporting
confidence: 93%
“…() indicate that plants from warmer sites tend to be larger in a community‐wide study and Meineri et al . () show an increased size at flowering for Veronica officinalis , both working in the same model system as us.…”
Section: Discussionsupporting
confidence: 53%
“…Geographical distance between sites is on average 15 km and ranges from 0·65 km (BOR2 and SUB2) to 175 km (BOR1 and BOR4) (Meineri et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Further details on site selection and characteristics can be found in Meineri et al . (, ) and Klanderud et al . ().…”
Section: Methodsmentioning
confidence: 92%